EFFICIENCY ANALYSIS OF ISLAMIC BANKING IN YEAR 2018 - 2023 USING STOCHASTIC FRONTIER ANALYSIS - Setiadi, Hendri; Heirunissa, Heirunissa; Widyowati, Mutiara Puspa (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2025)
ABSTRACTThis study aims to analyze the efficiency of 12 Islamic commercial banks and the market competition of Islamic commercial banks in Indonesia during 2018 to 2023. The data used is secondary data per quarter taken from each bank's website and from OJK. The method used in this study is Stochastic Frontier Analysis (SFA) with input variables, namely operating costs, labor costs, fixed assets, total assets, and third party funds, while the output variable is the total financing of Islamic commercial banks and the Panzar-Rosse method to measure the level of competition in the banking industry. The test results show the highest efficiency value for Category 2 Commercial Bank category by Muamalat Indonesia Bank with a score of 93,67%. The highest efficiency value for Islamic commercial banks in the Bank Group 3 category is Sharia Indonesia Bank with a score of 95,04%. In addition, the lowest efficient value for Category 1 Commercial Bank Islamic commercial banks is Aladin Sharia Bank with a score of 53,66%, and the lowest efficiency value for Bank Group 1 Islamic commercial banks is Aladin Sharia Bank with a score of 82,03%. Islamic commercial banks simultaneously in Category 1 Commercial Bank to Category 3 Commercial Bank and Bank Group 1 to Bank Group 3 show market competition classified as monopolistic competition and the market is not concentrated.ABSTRAKPenelitian ini bertujuan untuk menganalisis efisiensi 12 bank umum syariah dan daya saing pasar bank komersial syariah di Indonesia selama tahun 2018 hingga 2023. Data yang digunakan adalah data sekunder per kuartal yang diambil dari website masing-masing bank dan dari OJK. Metode yang digunakan dalam penelitian ini adalah Stochastic Frontier Analysis (SFA) dengan variabel input, yaitu biaya operasional, biaya tenaga kerja, aset tetap, total aset, dan dana pihak ketiga, sedangkan variabel output adalah total pembiayaan bank komersial syariah dan metode Panzar-Rosse untuk mengukur tingkat daya saing di industri perbankan. Hasil pengujian menunjukkan nilai efisiensi tertinggi untuk kategori BUKU 2 oleh Bank Muamalat Indonesia dengan skor 93,67%. Nilai efisiensi tertinggi untuk bank umum syariah dalam kategori KBMI 3 adalah Bank Syariah Indonesia dengan skor 95,04%. Selain itu, nilai efisiensi terendah untuk bank umum syariah BUKU 1 adalah Bank Aladin Syariah dengan skor 53,66%, dan nilai efisiensi terendah untuk bank komersial syariah KBMI 1 adalah Bank Aladin Syariah dengan skor 82,03%. Bank komersial syariah secara bersamaan di BUKU 1 hingga BUKU 3 dan KBMI 1 hingga KBMI 3 menunjukkan persaingan pasar yang diklasifikasikan sebagai persaingan monopolistik dan pasar tidak terkonsentrasi.